The Articulatory Phonetics of /r/ for Residual Speech Errors - Boyce, Suzanne E. (Seminars in Speech and Language, 2015)
Effective treatment for children with residual speech errors (RSEs) requires in-depth knowledge of articulatory phonetics, but this level of detail may not be provided as part of typical clinical coursework. At a time when new imaging technologies such as ultrasound continue to inform our clinical understanding of speech disorders, incorporating contemporary work in the basic articulatory sciences into clinical training becomes especially important. This is particularly the case for the speech sound most likely to persist among children with RSEs–the North American English rhotic sound, /r/. The goal of this article is to review important information about articulatory phonetics as it affects children with RSE who present with /r/ production difficulties. The data presented are largely drawn from ultrasound and magnetic resonance imaging studies. This information will be placed in a clinical context by comparing productions of typical adult speakers to successful versus misarticulated productions of two children with persistent /r/ difficulties.
Keywords: Articulation; speech production; speech sound disorders; tongue configurations